Deep electrical resistivity sounding across a major ice covered fault belt in Northern Victoria Land (East Antarctica) - ARMADILLO, EGIDIO; BOZZO, EMANUELE; FERRACCIOLI F.; TABELLARIO G. (Geophysical Research Letters, 2004)
A Geomagnetic Depth Sounding profile was performed across the glaciated Rennick Graben and the adjacent fault-bounded terranes of northern Victoria Land in East Antarctica. Induction arrows analysis and a 2D inversion model provide a unique deep electrical resistivity window beneath these fault zones. The electrical resistivity break across the Lanterman Fault is apparently restricted to the upper crust, suggesting that this strike-slip fault may not represent a deep lithospheric suture. Further east, a westward-dipping conductor is traced to a depth of 40 km beneath the Robertson Bay Terrane. It may image a remnant of the paleo-Pacific oceanic plate, which subducted beneath the Bowers Terrane. Within the Wilson Terrane, the Rennick Graben is an upper-crust resistive block. The Rennick Graben lacks a deep crustal or upper mantle conductor, in contrast to several continental rifts. However, similar resistive lower crust underlies some other major strike-slip fault belts.